Residence Patterns and Wayana Social Organization - Lapointe, Jean (Ann Arbor : University Microfilms, 1971)
Part I : Population and Milieu
Part II : Organization of Activities within the Settlement
Part III : Mobility
Part IV : Initiation Ceremony, Marriage and Kinship
Part V : Management of Tension, Treatment of Sickness, Shamanism
Ph.D., Anthropology, Columbia University, 1970
bibliogr.